National Character, Local Wisdom, and Citizenship Education: Building National Identity Through Education - Dadang Mulyana (Paspama Institute, 2024)
National identity is the core of the existence of a nation which is reflected in the values, norms and attitudes held by its citizens. Local wisdom, as a cultural heritage owned by local communities, is an important foundation in the formation of national character. Citizenship education acts as an instrument for internalizing national values and developing awareness of responsibility as citizens. This research examines the role of national character, local wisdom, and citizenship education in building national identity through the education system. This research uses a qualitative approach with descriptive methods. The research results show that a civic education learning approach based on local wisdom has a positive impact in increasing students' involvement in learning, broadening their understanding of citizenship concepts, and strengthening students' cultural identity. Through meaningful social interactions and collaboration within their local cultural context, students not only gain new knowledge, but also develop a deeper understanding of civic values and local wisdom. Thus, this approach has the potential to enrich students' learning experiences as well as facilitate a sustainable process of meaning formation in the context of their learning community.